Teaching English Vocabulary Through Pictures To Pre-Elementary School Students: A Case Study In TKIT Yaa - Bunaya Sragen 2004 / 2005 - Partini, Sri (2005)
Teaching English vocabulary to children is very useful especially to introduce simple English words. Teaching English through pictures is more effective, because children like pictures. Besides that, the children enjoy more and are attracted to learn. In the research, the writer is describing the implementation of teaching English vocabulary through pictures to children in pre-elementary school. The objectives of the research are to describe the activities of the teachers and the students in the impelementation of teaching vocabularies using picture, to describe the kinds of problems faced by the teachers and the students in teaching vocabulary through pictures at Yaa-Bunaya pre-elementary school, and to find the strengths and weaknesses of teaching vocabulary through pictures. In her research, the writer uses three techniques: observation, interview, and field notes. To get the data, the writer Yaa - Bunaya pre-elementary school to observes teaching-learning process. The writer did the observation from February 2005 until April 2005. The writer interviewed the headmaster and the teacher, to know more deeply about everything related to the research problem. Based on the teaching observation, the result of teaching vocabulary through pictures is satisfying. It can be proved from the students' activities in the classroom, students' motivation and interests. Based on the interview, the writer can conclude that there are some weaknesses found in the application of the method. First, the teacher is lack of developing the way of teaching English through pictures. Second, the schools pay less attention the facilities for supporting the teaching of English. The writer concludes that by using pictures, the students can learn vocabulary easily.